Juridical Analysis of Criminal Sanctions in Handling Cases of Sexual Abuse Crimes Committed by Teachers: A Study of Court Decision Number 1649/Pid.Sus/2020/PN.Mks - Eko Budi Santoso; M. Syahrul Borman; Nur Handayati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This research aims to analyze the application of material criminal law against perpetrators of sexual abuse crimes against children and examine the judge's considerations in sentencing in cases of sexual abuse against children committed by teachers. The study focuses on Court Decision Number 1649/Pid.Sus/2020/PN.Mks, where a Quran teacher was convicted of committing sexual abuse against several of his students. This normative legal research employs statutory and case approaches, analyzing primary legal materials including the Criminal Code (KUHP), Law Number 35 of 2014 concerning Child Protection, and the aforementioned court decision. The findings indicate that the application of material criminal law in this case has been in accordance with Article 82 paragraph (1), jo Article 76E of the Child Protection Law, where all elements of the crime were proven fulfilled. However, the judge's consideration in sentencing raises critical concerns regarding the application of aggravating factors. Under Article 82 paragraph (4) of the Child Protection Law, when sexual abuse is committed by educators, the punishment should be increased by one-third. The court sentenced the defendant to 6 years and 6 months imprisonment and a fine of Rp. 60,000,000, whereas according to the applicable law with aggravating factors, the sentence should have been 8 years and 8 months imprisonment. The study also identifies obstacles in handling such cases, including children's difficulty in revealing traumatic events, victims' fear and shame, limited witnesses, threats from perpetrators, and inadequate resources. The research recommends consistent application of sentence enhancement for perpetrators who are educators, improved inter-agency cooperation in handling child victims, enhanced school security measures, and comprehensive legal protection for child victims throughout the judicial process.